Monetary stance and favorableness of monetary policy in the media: The case of Viet Nam - Doan Ngoc Thang; Pham Thi Hoang Anh; Trinh Quang Long; Do Phu Dong; Luong Van Dat (Asian Development Bank Institute (ADBI), 2022)
This paper analyzes the effects of monetary stance on the media's favorable (or otherwise) attitude to the State Bank of Viet Nam's (SBV) monetary policy using monthly data from 2011 to 2021. Monetary stance is a multivariate index based on the growth rates of money supply and domestic credit. A large set of articles published in five Viet Nam daily newspapers is utilized to construct a view of the media's favorableness to the monetary policy. Our main findings are that a change in monetary stance from easing to neutral/tightening, or from neutral to tightening is greatly appreciated by the media. This effect is negatively moderated by the volatility of the stock exchange index. Our findings are robust for alternative measures of media's favorableness, monetary policy variables, and when controlling the endogeneity problem. These findings have important policy implications for implementing SBV's monetary policy.
Keywords: E52; E58; 330; monetary policy; monetary stance; media coverage; media favorableness; communication